Kontribusi Kekuatan Otot Lengan dan Konsentrasi terhadap Keterampilan Shooting Free Throw Atlet Bola Basket - Mustika, Fitrya; Rifki, Muhammad Sazeli; Sin, Tjung Haw; Gusril, Gusril; Mariati, Sari; Budiwanto, Adri (Jurnal Sporta Saintika, 2024)
This research focuses on the low free throw ability of basketball athletes in Binuang Sakti, Sijunjung Regency, with the aim of identifying and revealing the effect of arm muscle strength and concentration on free throw ability. The research method used is path analysis. The study population consisted of 39 Binuang Sakti basketball athletes, Sijunjung Regency, consisting of 25 men and 14 women. The sample was taken using purposive sampling technique, which selected 24 male athletes. Data were collected through a push-up test to measure arm muscle strength, concentration test grid to measure concentration, and free throw test with 10 repetitions. free throw test with 10 repetitions. The results showed: (1) There is direct effect of arm muscle strength on free throw ability, with a Py1 value of 0.235 or 6.4%. Py1 value of 0.235 or 6.4%. (2) There is a direct effect of concentration on free throw ability, with a Py3 value of 0.587 or 34.4%. (3) There is an indirect effect of arm muscle strength on concentration, with a P31.py3 value of 0.246 or 6.1%. (4) Overall, arm muscle strength strength and concentration have a significant influence on the ability free throw ability of Binuang Sakti basketball athletes, Sijunjung Regency, with a value of Rsquare value of 0.497 or 49.7%. Keywords: Basketball, Muscle Strength, Concentration, Penalty Shots